A fully hydrodynamic urban flood modelling system representing buildings, green space and interventions. (November 2018) - Glenis, V.; Kutija, V.; Kilsby, C.G.
Abstract: City Catchment Analysis Tool – CityCAT-is a novel software system for rapid assessment of combined pluvial and fluvial flood risk using a unique combination of: efficient software architecture throughout and especially in the numerical part; use of standard, readily available data sets; efficient algorithms for grid generation; and robust and accurate solutions of the flow equations. It is based on advanced software architecture and accurate solutions for complex free-surface flow over the terrain distinguishing between permeable and impermeable surfaces and taking into account effects of man-made features such as buildings as obstacles to flow. The software is firstly rigorously validated with demanding test cases based on analytical solutions and laboratory studies. Then the unique capability for assessment of the effectiveness of specific flood alleviation interventions across large urban domains, such as roof storage on buildings or introduction of permeable surfaces, is demonstrated. Highlights: An object-oriented 2D hydrodynamic model is presented for use in urban flood analysis and design. The model retains accuracy in representing complex flows while allowing rapid modelling of large city domains. Buildings and green urban infrastructure are flexibly and accurately represented.